La pêche dans le droit romain - Hallé, Michel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
Looking back to the Roman era, one can see that the regulation of fisheries already formed a coherent whole which is still interesting to analyse today. The oceans, seas and their shores are res communes, meaning that no one can own these things, or that everyone can make use of these things freely as long as this does not interfere with someone else's right. By contrast, rivers and their banks as well as harbours are classified res publicae, i.e. State property, but assigned to common use. Some fishing places were the exclusive property of the Roman State (res in patrimonio populi) and liable to be leased. Fishing was a legally well defined activity, under strict control by the State: later generations have drawn inspiration from Roman rules in this field.